A systematic review of research on pre-service TESOL teachers’ emotions - Saadet Korucu Kış (Üniversite Araştırmaları Dergisi)
The study of pre-service teachers’ emotions has long been marginalized within the field of teaching English to speakers of other languages (TESOL). Yet, with the advent of a sociocultural turn in the field and an emotional turn in educational science, there has been growing interest in the role of emotions in would-be teachers’ professional learning. The purpose of this study is to examine the demographic (i.e. year of publication, contributing countries and methodologies used) and topical trends concerning pre-service teacher emotionality in TESOL teacher education. For this purpose, studies published in journals that were included in Social Science Citation Index (SSCI) were reviewed and a total of 19 research articles were analyzed using both deductive and inductive analysis techniques. Concerning the demographic trends, the findings revealed that there has been an increase in the number of research articles within the last decade. Turkey and China are among the major contributing countries and the most frequently used research methodology is qualitative method. As to topic trends, “Emotions and Identity Formation”, “Emotions in relation to Language Learning” and “Emotional Responses to University Coursework” are found to be as the most popular research topics. As a result of the analysis, current gaps in research on TESOL education are identified and suggestions are made for future work.